An Analysis on Farmer Rights in International Trade Under Indonesian Law - Moch Najib, Imanullah (Technium Social Sciences Journal, 2020)
The aims of this research were to examine the legal protection on the farmer rights in international trade under Indonesian law. The research was important to provide various alternative solutions over the problem of inabilities of farmer to be a subject of international trade and to review whether the Indonesian Government gave legal protection to farmer rights. It was an empirical legal research, which using primary and secondary data. Primary data was collected from the respondents and informants while the secondary ones were taken from primary and secondary legal materials. The validity of data used sources triangulation method while all of data were analysed by analysis of editing style through legal interpretation. The result showed that Indonesian Government through enactment of its legislation has not been providing the legal protection to the farmer rights in international trade optimally. Moreover, this study was expected to contribute in reforming over legislation that regulates the protection of farmer rights.